ANALISIS WACANA TENTANG SARAF PADA BUKU PAKET BIOLOGI 2 UNTUK SLTP DAN SMU - Jajat Sudrajat, - (2002)
textbook elaboration with demand of prevailing GBPP curriculum, and also application of spiral approach. Analysis in this study is conducted in discourse material which is considered abstract by students or teachers that is nerve. Analyzing process is started by changing original text, the process is placed on analysis table. Each of basic paragraph is placed on the columns which is the number is adjusted with number of paragraph. All propositions which is excluded is kept in the columns which in accord with macro level started from micro proposition until the most abstract macro proposition. The form ofproposition use macro regulation which is consists of abolition, generalization and construction. Results of analyses nerve basic text in Junior High School, there is 119 of proposition which is consist of 22 proposition ofmacro I, 7 proposition of macro II, 4 macro III, 1 macro IV and 74 which form micro proposition. Such proposition form macro structure such as text representation which have vertical dimension (progression) and horizontal dimension (elaboration). In macro structure there is progression and elaboration differences, which shows 71%. Spiralization and continuation in material comprehension is found from Junior High School textbook to Senior High School Biology 2textbook. In this study is gained picture analyses result which show picture from Junior High School textbook is more complete compared with picture from Senior High School textbook. About global nerve System and Coordination Function in Junior High School Biology 2 textbook is gained more progression level than nerve in Senior High School Biology 2 textbook. Both of textbooks for Junior and Senior High School has followed model diagram of text representation, because after being analyzed about the depth and material liberation is traced in complete macro structure with proposition which is similar with the author outline which very detail so before the writer express his idea in more detail writing, he can edit parts which will be written so there is suitability between GBPP with writing result (textbook). Beside spiral model is occurred although the Junior and Senior High School textbooks author is not in the same team. This analyses result is recommended to Biology teacher, the author of Biology textbooks, and the textbooks company. Analisis wacana ini merupakan studi untuk mengetahui kesesuaian progresi dan elaborasi buku paket dengan tuntutan GBPP kurikuium yang berlaku, serta penerapan pendekatan spiral. Analisis dalam penelitian ini dilakukan pada materi wacana yang dianggap abstrak oleh siswa maupun guru yaitu saraf. Proses menganalisis dimulai dengan mengubah teks asli menjadi teks dasar melalui penghalusan teks, prosesnya ditempatkan pada tabel analisis. Setiap alinea teks dasar ditempatkan pada kolom-kolom yang jumlahnya di sesuaikan dengan jumlah alinea. Seluruh proposisi yang dikeluarkan disimpan pada kolom sesuai tingkat makro mulai dari proposisi mikro sampai proposisi makro yang paling abstrak. Pembentukan proposisi menggunakan aturan makro yang terdiri dari penghapusan, generalisasi dan konstruksi. Hasil analisis teks dasar saraf SLTP, terdapat 119 proposisi yang terdiri dari 22 proposisi makro I, 7 proposisi makro II, 1 proposisi makro III dan 90 sebagai proposisi mikro. Sedangkan hasil analisis sarafSMUterdapat 118 proposisi yangterdiri dari 29 proposisi makro I, 10makro II, 4 makro tiga, 1 makro IVdan 74 yang membentuk proposisi mikro. Proposisiproposisi tersebut membentuk struktur makro berupa representasi teks yang memiliki dimensi vertikal (progresi) dan dimensi horisontal (elaborasi). Pada struktur makro terdapat perbedaan progresi dan elaborasi, yang menunjidckan 71 %. Spiralisasi atau kesinambungan dan pendalaman materiditemukan dari buku paket SLTP ke buku paket Biologi 2 SMU. Dalam studi ini didapat hasil analisis gambar yang menunjukkan gambar buku paket SLTP lebih lengkap dibanding SMU. Mengenai struktur global Sistem saraf dan Fungsi Koordinasi pada buku paket Biologi 2 SLTP diperoleh tingkat progresi lebih banyak dibanding dengan sarafpada bukupaketBiblogi 2 SMU. Keduabuku paketBiologi untuk SLTP dan SMU sudah mengikuti diagram model representasi teks, karena setelah dianalisis kedalaman dan keleluasaan materi terlacak dalam sruktur makro lengkap dengan proposisi yang mirip dengan outline penulis yang sangat rinci sehingga sebelum penulis menuangkan gagasannya dalam bentuk tulisanyang lebih rinci, sudah bisa menyunting bagian-bagian yang akan ditulisnya sehingga bisa terjadi kesesuaian antara GBPP dengan hasil tulisan (buku paket). Selain itu model spiralpun terjadi walaupun penulis buku paketSLTPdan SMUbukan tim yang sama. Hasil analisis ini direkomendasikan kepada pengajar Biologi, penulis buku paket Biologi, dan perusahaan pembuat buku paket.